Human Placental Allograft Membranes: Promising Role in Cardiac Surgery and Repair - Hitscherich, Pamela G.; Chnari, Evangelia; Deckwa, Jessa; Long, Marc; Khalpey, Zain (Frontiers in Cardiovascular Medicine, 2022)
Despite the immense investment in research devoted to cardiovascular diseases, mechanisms of progression and potential treatments, it remains one of the leading causes of death in the world. Cellular based strategies have been explored for decades, having mixed results, while more recently inflammation and its role in healing, regeneration and disease progression has taken center stage. Placental membranes are immune privileged tissues whose native function is acting as a protective barrier during fetal development, a state which fosters regeneration and healing. Their unique properties stem from a complex composition of extracellular matrix, growth factors and cytokines involved in cellular growth, survival, and inflammation modulation. Placental allograft membranes have been used successfully in complex wound applications but their potential in cardiac wounds has only begun to be explored. Although limited, pre-clinical studies demonstrated benefits when using placental membranes compared to other standard of care options for pericardial repair or infarct wound covering, facilitating cardiomyogenesis of stem cell populations in vitro and supporting functional performance in vivo. Early clinical evidence also suggested use of placental allograft membranes as a cardiac wound covering with the potential to mitigate the predominantly inflammatory environment such as pericarditis and prevention of new onset post-operative atrial fibrillation. Together, these studies demonstrate the promising translational potential of placental allograft membranes as post-surgical cardiac wound coverings. However, the small number of publications on this topic highlights the need for further studies to better understand how to support the safe and efficient use of placenta allograft membranes in cardiac surgery.